The Turning Point of Woman from Victorian Stereotype into Liberal Model in Sons and lovers by D.H. Lawrence - Mohammed Haqi Khaleel Alazzawi, Lect. Dr (lark, 2023)
Via Sons and Lovers, D,H, Lawrence aims to bring about attitudinal and legislative changes that enable woman to achieve her rights. His work is a project that refuses the Victorian stereotype of woman—the housewife. It is a paradigm shift in social freedom of woman, that helps her free herself from dominant sociocultural patterns. His project draws its power from his daring female characters. Actually they are functioned to agitate the woman movement of liberation at Lawrence’s time.